HUBUNGAN ASUPAN MAKAN DAN AKTIVITAS FISIK TERHADAP STATUS GIZI SISWA SMKN 1 KOTA TEGAL - Risky Fatikasari; Anggray Duvita Wahyani; Rifatul Masrikhiyah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2022)
Humans need nutrients to live, grow, develop, move, and maintain health. Nutritional needs are not the same for everyone. The growth and development of school-age children, especially teenagers, depends on providing adequate and balanced nutrition. Teenagers have more a lot of activities that affect the amount of energy the body needs. If there is an imbalance between food intake and output of energy for a long time, it can also affect the value of a person's nutritional status. Nutritional status is one of the important elements in shaping health status. Nutritional status is a condition caused by a balance between food intake and nutritional needs. The purpose of this study was to determine the relationship between food intake, physical activity, and nutritional status in students of Vocation High School 1 Tegal City. The research design use analytic with a cross sectional design approach. The research instrument use a questionnaire and direct measurement. The number of samples in this study are 33 people. Sampling methode use simple random sampling. Statistical tests were carried out using the Somers’d test with a value of 0,05. If the p value is less than 0,05 then the results of the study are meaningful. From the results of the analysis, it finds that there is a relationship between food intake and nutritional status, and there was no relationship between physical activity and nutritional status.